Perception and knowledge of Saudi women about water birth: A cross-sectional study - Saja Bashaikh; Fouzia Mahboub; Abeer Orabi (Belitung Nursing Journal, 2022)
Background: Water birth has been considered an efficient non-pharmacological modality with numerous maternal and neonatal benefits as well as rare complications. Perception and knowledge about water birth can affect women’s decisions in the future. Few available studies addressed this area in Saudi Arabia. Thus, the current research fills this gap and contributes to further understanding this phenomenon. Objective: This study aimed to assess the perception and knowledge of Saudi women about water birth. Methods: A cross-sectional study was employed among 388 Saudi women conveniently enrolled for the study. An online questionnaire that included four sections: sociodemographic characteristics, obstetrical history, perception, and knowledge of water birth, was used for data collection. Descriptive statistics (frequencies, percentages, means, and standard deviations) and inferential statistics (Chi-Square, Fisher Exact, and t-tests) were used for data analysis. Results: The participants’ mean age was 34.91 ± 8.851, with 83.2% of them highly educated. The mean number of deliveries was 3.36 ± 2.167, with 60% having no history of abortion. Less than half of the participants (40.2%) preferred to have a water delivery. Of the total participants, 96.4% had a fair knowledge level, and 3.6% had a good knowledge of water delivery. A significant relationship was found between age, educational course, and the knowledge of the participants about water delivery (p <0.05). Conclusion: Most Saudi women had a fair knowledge of water birth; however, they wanted more information on it. It is recommended that midwives and nurses broaden their understanding of water birth and enhance its practice in order to educate and inspire women to make informed decisions about all available childbirth delivery methods, including water birth.